Книжный вор: [роман] / Маркус Зусак ; перевод с английского Николая Мезина - Зусак Маркус (Яркие страницы, 2020)
Экземпляры: аб (20210209) / Инвентарный номер: 45557 / Цена: / Авт.знак: З-95 / ГРНТИ: 17.82.31 / ББК: 84(8Авс)-44